An oncogenic role for transcription factor ERG in prostate cancer progression: promoting androgen-independent growth and survival. - Sng, Noel Yan Wei. (2011)
The discovery of recurrent gene fusions between AR-regulated transmembrane protease and ERG has shed new light on the molecular events that may contribute to the development and progression of prostate cancer. Since then, there has been increasing evidence from clinical studies reporting that ERG is overexpressed in many patients with hormone refractory prostate cancer. However, the role of ERG in androgen independent prostate cancer is still poorly understood. In this study, we sought to investigate the oncogenic role of ERG in two androgen-dependent cell lines, VCaP and LNCaP under androgen-depleted conditions. Using overexpression and knockdown approaches, we analysed the ability of ERG in proliferation by BrdU flow cytometry assay; and in apoptosis by propidium iodide flow cytometry assay. We showed that ERG overexpression increases cell proliferation and reduces cell apoptosis under androgen-depleted conditions. Conversely, ERG knockdown by small interfering RNA decreases cell proliferation and increases apoptosis. We also demonstrated that HDAC inhibitor, Trichostatin A (TSA), reduce ERG-mediated proliferation and cell survival. Taken together, these findings suggest that ERG plays a critical role in promoting androgen-independent cell proliferation and survival; and its oncogenic effect is at least in part mediated by HDAC.